2021
DOI: 10.1155/2021/8871631
|View full text |Cite
|
Sign up to set email alerts
|

Nesting Ecology of West African Dwarf Crocodiles in a Heavily Disturbed Landscape in Chirehin, Ghana

Abstract: West African dwarf crocodiles (Osteolaemus sp. nov. cf. tetraspis) are among the most threatened crocodilians in the world due to unregulated hunting and habitat loss-related population decline. Despite this, many questions about their basic ecology remain unanswered and this inadequate data hampers effective dwarf crocodile management. We describe incubation temperature, nesting success, hatching rate, and clutch size of West African dwarf crocodiles. We monitored 18 nests from the 2017 and 2018 nesting seaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Temperatures in nests of P. trigonatus in central Amazonia were significantly related to rainfall, but not air temperature (Magnusson et al, 1990). Amoah et al (2021) also found only a weak relationship between nest and air temperatures in Osteolaemus sp. Nov. cf.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Temperatures in nests of P. trigonatus in central Amazonia were significantly related to rainfall, but not air temperature (Magnusson et al, 1990). Amoah et al (2021) also found only a weak relationship between nest and air temperatures in Osteolaemus sp. Nov. cf.…”
Section: Discussionmentioning
confidence: 81%
“…nov. cf. tetraspis, in Africa (Amoah et al, 2021). In captive situations, P. palpebrosus eggs are incubated at a temperature between 28 o C to 32 o C for an incubation period of 96 to 130 days (Medem, 1971(Medem, , 1972Rugeles, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The depositional systems at sites preserving Kinyang and Brochuchus all reflect mixed riparian woodlands and mixed open habitats that formed under comparatively dry conditions (Butts et al, 2018; Driese et al, 2016; Liutkus‐Pierce et al, 2019; Lukens et al, 2017; Michel et al, 2020; Retallack et al, 2002). But living dwarf crocodiles are not restricted to closed‐canopy rain forests; they can be found in riparian woodlands and seasonal wetlands (e.g., Eaton, 2010; Ceríaco & de Sá, 2018; Amoah et al, 2021). Thus, the kinds of biomes that dominated Early to Middle Miocene sites preserving generalized osteolaemines might not reflect different ecological preferences from modern Osteolaemus .…”
Section: Discussionmentioning
confidence: 99%
“…These, in turn, are thought to have led to diminishing woodlands and expansion of C 4 plants (e.g., Feakins et al, 2013; Jacobs et al, 2010; Linder, 2017; Saarinen et al, 2020). This prompted Cossette et al (2020) to suggest that changes in crocodylian faunas might have reflected changes in vegetation; modern African dwarf crocodiles ( Osteolaemus Cope, 1861; Figure 1b) are generally limited to forested wetlands (Amoah et al, 2021; Eaton, 2010; Kofron, 1992; Leaché et al, 2006; Riley & Huchzermeyer, 1999; Smolensky, 2015; Waitkuwait, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…obs. ; Amoah et al 2021). Also, the current studies on crocodiles do not show a clear representation of urban ecosystems which are unique habitats that required targeted research and data for fuelling targeted urban crocodile conservation actions (Gross 2002).…”
Section: Introductionmentioning
confidence: 99%